2020
DOI: 10.3906/elk-1906-151
|View full text |Cite
|
Sign up to set email alerts
|

On the automorphisms and isomorphisms of MDS matrices and their efficient implementations

Abstract: In this paper, we explicitly define the automorphisms of MDS matrices over the same binary extension field.By extending this idea, we present the isomorphisms between MDS matrices over F2m and MDS matrices over F 2 mt , where t ≥ 1 and m > 1 , which preserves the software implementation properties in view of XOR operations and table lookups of any given MDS matrix over F2m . Then we propose a novel method to obtain distinct functions related to these automorphisms and isomorphisms to be used in generating isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Then, 70,344 ( ) representative involutory MDS matrices cannot be generated by Hadamard matrix form. That means, by using the method given in Sakallı et al (2020) , one can map these representative involutory MDS matrices in order to obtain directly isomorphic counterparts over . Note that there are 4 isomorphisms from the finite field (defined by any irreducible polynomial) to the finite field (defined by any irreducible polynomial).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 70,344 ( ) representative involutory MDS matrices cannot be generated by Hadamard matrix form. That means, by using the method given in Sakallı et al (2020) , one can map these representative involutory MDS matrices in order to obtain directly isomorphic counterparts over . Note that there are 4 isomorphisms from the finite field (defined by any irreducible polynomial) to the finite field (defined by any irreducible polynomial).…”
Section: Resultsmentioning
confidence: 99%
“…To handle this problem, the Generalized Hadamard (shortly GHadamard) matrix form, a hybrid construction method, was proposed in Pehlivanoğlu et al (2018) . Overall, in Sakallı et al (2020) , the authors proposed a complementary method for the current construction methods in the literature, which generates isomorphic MDS matrices (new MDS matrices from the implementation point of view) from any existing MDS matrix (due to its ground field structure). All these methods can be evaluated within the local optimization category that focuses on the coefficients of a given matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MDS matrices are used in stream ciphers ( Watanabe et al, 2002 ) and hash functions ( Barreto, Rijmen & Nv, 2000 ; Choy et al, 2012 ; Gazzoni Filho, Barreto & Rijmen, 2006 ; Gauravaram et al, 2009 ; Guo, Peyrin & Poschmann, 2011 ), as indicated in various studies. In the literature, there are different types of methods to construct efficient MDS matrices, such as direct construction ( Cui, Jin & Kong, 2015 ; Sajadieh et al, 2012 ; Gupta & Ray, 2013 ; Güzel et al, 2019 ), search based construction ( Wu, Wang & Wu, 2013 ; Chand Gupta & Ghosh Ray, 2014 ; Li & Wang, 2016 ; Sarkar & Syed, 2016 , 2017 ; Sakalli et al, 2020 ), and hybrid construction ( Pehlivanoğlu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%